Binge Watching Netflix in Pakistan: Factors and Psychological Impacts on University Students in Lahore - Kashaf Adnan,; Ammar Yasir,; Maheen Baloch, (Journal of Peace, Development and Communication, 2024)
This study explore the binge-watching phenomenon among university students in Lahore, focusing on their motivations and the psychological impacts of extensive Netflix consumption. Utilizing the Uses and Gratification Theory as a framework, the research aims to provide insights into why students engage in binge-watching and how it affects their well-being. Semi-structured interviews were conducted with 12 participants from three universities in Lahore, aged 19 to 24, to gather qualitative data. Thematic analysis identified seven key themes: boredom, self-gratification, post-binge-watching depression, para-social attachment, social comparison, isolation, and procrastination. These themes explained the nature of binge-watching behaviors and their repercussions on mental health and daily routines.The findings suggest that while binge-watching serves as a means to alleviate boredom and stress, it also leads to negative psychological outcomes such as loneliness, depression, and emotional detachment from reality. Participants expressed a strong affinity for media characters and reported using Netflix to fulfill emotional needs and escape from academic pressures and pandemic-related isolation. Understanding the motivations and consequences of binge-watching among university students is significant for developing targeted interventions that promote healthy media consumption habits and support mental well-being in academic setting